Investigation of high-speed badminton racket kinematics by motion capture - Kwan, M.; Andersen, M. S.; Cheng, C. L.; Tang, W. T.; Rasmussen, J. (Sports Engineering, 2011)
The kinematics of a badminton racket during a smash stroke was observed in this study with the purpose of investigating stroke dynamics and racket behaviour. Motion capture measurements of the racket during several smash strokes performed by three players of different skill levels indicated a clear increase in racket velocity at impact with increasing skill level. Variations between translational and rotational contributions to the impact speed could also be seen between the players. The advanced player produced a much higher peak angular velocity and also relied much less on translation, with a translational velocity of only 8% of the total velocity versus the 20% for the recreational player. It is proposed that, as an alternative to shuttlecock speeds, racket head speed measurements can be used as an indicator of performance, and can also provide some insight into the interaction between the racket and player.